2015
DOI: 10.1021/acs.jpclett.5b01698
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer Dynamics from Organometal Halide Perovskite to Polymeric Hole Transport Materials in Hybrid Solar Cells

Abstract: Organometal halide perovskites have emerged as promising next-generation solar cell technologies presenting outstanding efficiencies. However, many questions concerning their working principles remain to be answered. Here, we present a detailed study of hole transfer dynamics into polymeric hole transporting materials (HTMs), poly(triarylamine) (PTAA), poly(3-hexylthiophee-2,5-diyl (P3HT), and poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene)-alt-4,7-(2,1,3-benzothiadiazole) (PCPDTBT). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 29 publications
4
76
0
Order By: Relevance
“…2a). The TA spectral features of CH(NH 2 ) 2 PbBr 3 perovskite are quite similar to those observed in other related perovskites, thus could be explained using existing conceptions [19,20]. The bleaching band is attributed to the valence band (VB) depopulation [21] and the positive long-lived induced absorption band in a 490-520 nm region arises due to refractive index change [20] The bleaching band shows an initial fast red shift, which could be attributed to the exciton-exciton interaction [22].…”
Section: Resultssupporting
confidence: 76%
“…2a). The TA spectral features of CH(NH 2 ) 2 PbBr 3 perovskite are quite similar to those observed in other related perovskites, thus could be explained using existing conceptions [19,20]. The bleaching band is attributed to the valence band (VB) depopulation [21] and the positive long-lived induced absorption band in a 490-520 nm region arises due to refractive index change [20] The bleaching band shows an initial fast red shift, which could be attributed to the exciton-exciton interaction [22].…”
Section: Resultssupporting
confidence: 76%
“…The time constant of the hole injection from CH3NH3PbI 3 (MAPbI 3 ) to spiro-OMeTAD in the previous reports, for example, scattered widely from <80 fs [7] to 0.7 ps [8,9] to 8 ps [10]. The hole injection to NiO x was reported to be complete on sub-picosecond time scale [11], whereas those * ishioka.kunie@nims.go.jp to poly(triarylamine) (PTAA), poly(3-hexylthiophee-2,5-diyl (P3HT), and poly [2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta [2,1-b;3,4-b'] dithiophene)-alt-4,7-(2,1,3-benzothiadiazole) (PCPDTBT) were reported to occur on sub-nanosecond time scales [12]. The wide range of the time scale over orders of magnitude appear puzzling at first glance, because the investigated HTMs have relatively similar valence band energies.…”
mentioning
confidence: 99%
“…16). 115 Consequently, it has been shown that energy transfer from the photoexcited P3HT to MAPbI 3 can occur, provided the excitation in the P3HT is in close proximity to the P3HT | MAPbI 3 interface. In this way, P3HT can be used to sensitize MAPbI 3 and excitations in the HTM are not lost for photocurrent generation 115 .…”
Section: Perovskite Photovoltaicsmentioning
confidence: 99%
“… 115 Consequently, it has been shown that energy transfer from the photoexcited P3HT to MAPbI 3 can occur, provided the excitation in the P3HT is in close proximity to the P3HT | MAPbI 3 interface. In this way, P3HT can be used to sensitize MAPbI 3 and excitations in the HTM are not lost for photocurrent generation 115 . The differences in hole transfer rates between small molecular HTMs as spiro -MeOTAD and polymeric HTMs as P3HT might be partially explained by poor physical contact in the case of the polymers, given that the thermodynamic driving force for hole transfer to all investigated HTMs is rather similar.…”
Section: Perovskite Photovoltaicsmentioning
confidence: 99%